An Auto‐Inductive Cascade for the Optical Sensing of Thiols in Aqueous Media: Application in the Detection of a VX Nerve Agent Mimic. (3rd July 2017) - Sun, Xiaolong; Anslyn, Eric V.
Abstract: A new auto‐inductive protocol employs a Meldrum's‐acid‐based conjugate acceptor (1 ) as a latent source of thiol for signal amplification, as well as optical detection of thiols. The auto‐induction is initiated by a thiol‐disulfide exchange that leads to the generation of β‐mercaptoethanol, which in turn decouples the conjugate acceptor to release more thiols, resulting in a self‐propagating cycle that continues until all the conjugate acceptor is consumed. Using1 in a two‐step integrated protocol yields a rapid, sensitive, and precise diagnostic assay for the ultratrace quantitation of a thiophosphate nerve agent surrogate.